Impact of N-Acetylcysteine on the Gut Microbiota in the Piglets Infected With Porcine Epidemic Diarrhea Virus - Wu, Tao; Lyu, Yang; Li, Xueni; Wu, Mengjun; Yu, Kui; Li, Siyuan; Ji, Changzheng; Zhang, Qian; Zhang, Yanyan; Zhao, Di; Yi, Dan; Hou, Yongqing (Frontiers in Veterinary Science, 2021)
This study was to investigate the impact of N-acetylcysteine (NAC) on the gut microbiota in the healthy piglets and the piglets infected with porcine epidemic diarrhoea virus (PEDV). Forty 7-day-old piglets were allocated into four groups: control group, NAC group (supplemented with 50 mg/kg body weight NAC), PEDV group (inoculated with 104.5 TCID50 PEDV), and PEDV+NAC group (PEDV infection + NAC supplementation). The intestinal content was collected for DNA extraction and Illumina sequencing. The PEDV-infected piglets displayed distinct bacterial communities compared to the healthy piglets. PEDV infection decreased the abundance of Shigella and increased the abundance of Lactobacillus, Odoribacter, Anaerovibrio, Helicobacter, unclassified Lachnospiraceae and Sutterella; affected several functions associated with metabolism, barrier and immune. NAC supplementation decreased the abundance of unclassified Rikenellaceae and increased the abundance of Lactobacillus, Streptococcus and Enterococcus in the healthy piglets, decreased the abundance of Oscillospira and Prevotella and increased the abundance of Lactobacillus in the PEDV-infected piglets; altered multiple functions involving in amino acid metabolism, cell signalling, cellular community, disease-related pathways, endocrine and excretory system. In conclusion, PEDV infection caused severe dysbiosis of gut microbiome, whereas NAC supplementation played a positive role in regulating the gut microbiome during PEDV infection. Therefore, substances that can regulate gut microbiota could be ideal candidates to prevent or treat PEDV infection.